Implementation of Teacher Competency Policy at SDN 2 Lubuk Seberuk, School of Mover Class II - Septri Yuspita; Nur Ahyani; Muhammad Fahmi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This thesis examines the implementation of the teacher competency policy at SDN 2 Lubuk Seberuk, a second-cohort